Awareness of gestational diabetes mellitus foetal-maternal risks: an Italian cohort study on pregnant women - Paola Quaresima; Federica Visconti; Fabiana Interlandi; Luigi Puccio; Patrizia Caroleo; Giuseppina Amendola; Michele Morelli; Roberta Venturella; Costantino Di Carlo (BMC Pregnancy and Childbirth, 2021)
Abstract Background Gestational diabetes mellitus (GDM) incidence is increasing worldwide. It represents a major risk factor for adverse foetal-maternal outcomes. Awareness among women in regard to GDM-related risks (in particular foetus ones) has been proven to have an impact on compliance with recommendations. Therefore we aimed to evaluate the efficacy of our post-diagnosis counselling, that informs affected women of the GDM related risks for complications, in determining an adequate level of understanding. Method This is a cohort study involving 400 women undergoing the 24-28 weeks 75 g oral glucose tolerance test. Two hundred women diagnosed with GDM received the post-diagnosis counselling (treatment group) and two hundred women diagnosed without did not receive any counselling (control group). Both populations were surveyed with a 5 question questionnaire regarding their awareness about GDM foetal-maternal related risks. Their level of education about GDM foetal-maternal related risks, estimated according to the number of correct answers, was scored as: primary (score 0-1), secondary (score 2-3) or tertiary (score 4-5). Results Most of the women in the treatment group after receiving the post-diagnosis counselling have demonstrated a secondary level of education 132/200 (66%). Their mean level of awareness was higher in comparison to the control group 2.6 ± 1.8 (SD) versus 2.14 ± 1.8 (SD) p value = 0.012. In particular, they’ve demonstrated to be more aware of the risks for the foetus to become macrosomic (p = 0.004) or to die in utero (p = 0.0001). A high level of education and to have had previous pregnancies positively affected correct answers. Conclusions Our post-diagnosis counselling has played a role in improving women awareness about GDM foetal-maternal related risks. Future study will explore the impact of women’s level of awareness on glycaemic control.